Pengaruh Ekstrak Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Kadar Kolesterol Pada Tikus Putih (Rattus norvegicus) Yang Diinduksi LDL - Zulfikar, Zulfikar; Ramadhan, Achmad; Mardin, Sutrisnawati; Isnainar, Isnainar; Budiarsa, I Made; Masrianih, Masrianih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of Roselle flower extract (Hibiscus sabdariffa L.) on cholesterol levels in White Rats (Rattus norvegicus) induced by LDL. The research method used is a Laboratory experimental method with a Completely Randomized Design (CRD) pattern. The number of samples used was 24 White Rats consisting of 6 treatment groups and 4 replications. The normal control group (KN) is a group that is only given food and drink, the negative control group (K-) is given LDL induction for 30 days, the positive control group (K+) is given LDL induction for 30 days and simvastatin, groups PI, PII and PIII are given LDL induction for 30 days and Roselle flower extract doses of 50 mg/kg BW, 100 mg/kg BW and 150 mg/kg BW for 21 days. The data obtained were tabulated and analyzed by the one-way ANOVA statistical test using SPSS version-30. The results showed that Roselle flower extract positively contains bioactive compounds such as flavonoids and tannins and has a significant effect (p<0.05) on reducing cholesterol levels in White Rats induced by LDL. The effective dose to reduce cholesterol levels is a dose of 100 mg/kg BW andÂ 150Â mg/kgÂ BW.